Valorização do conhecimento científico no currículo do município de Cascavel (PR): reflexões a partir da pedagogia histórico crítica - Marmentini, Josiane de Kassia (2024)
The object of this dissertation is to study the curriculum of the Municipal Public School Network of Cascavel - PR and the dissemination of scientific knowledge. The justification for this research lies in the singular importance of a curriculum that praises scientific expertise to face the complexity of the contemporary world marked by negationism and fake news. The History of Education is an instrument for understanding the transformations and current challenges in education. The aim is to discuss the curriculum as an instance of valuing, disseminating, and disseminating scientific knowledge, based on authors who formulated their theories based on the assumptions of Historical-Dialectical Materialism. Methodologically, this is a bibliographical and documentary study. The approach of Historical-Critical Pedagogy establishes an educational environment that goes beyond the mere transmission of information and a scientific understanding of society and its contradictions. The sources include the Curriculum of Cascavel - PR, the academic productions available on the Portal of the Coordination for the Improvement of Higher Education Personnel (Capes), and the Digital Library of Theses and Dissertations (BDTD), selected because they were related to the theme of Historical-Critical Pedagogy and supported by the theoretical-methodological contributions of Historical-Dialectical Materialism. The dissertation addresses the democratization of scientific knowledge in contemporary public schools, discusses the role of the teacher and the integration of Historical Critical Pedagogy in the western region of Paraná, offers an analysis of the Cascavel Curriculum, as well as the possibilities and challenges in valuing science and Historical-Critical Pedagogy. The results of the research indicate that the approach of the National Common Core Curriculum (BNCC), which prioritizes technical training geared towards the job market, contrasts with the historical-critical approach of the Curriculum of Cascavel - PR, which values the transmission of essential knowledge for integral human formation. The attempt to reconcile these perspectives has resulted in the superficiality of scientific knowledge, especially in times marked by negationism, compromising the dissemination of science. However, how teachers work can influence the implementation of the historical-critical approach.